Children of Organized Crime Offenders: Like Father, Like Child? An Explorative and Qualitative Study Into Mechanisms of Intergenerational (Dis)Continuity in Organized Crime Families - van Dijk, Meintje (European journal on criminal policy and research, 2019)
This qualitative descriptive study aims to explore (1) the extent of intergenerational continuity of crime in families of organized crime offenders, (2) the mechanisms underlying this phenomenon and (3) the mechanisms underlying intergenerational discontinuity. The study comprised a descriptive analysis of the available numeric information on 25 organized crime offenders based in Amsterdam and their 48 children of at least 19 years of age and a more qualitative in-depth analysis of police files, justice department files and child protection service files of all the family members of 14 of the 25 families. Additionally, interviews with employees of the involved organizations were conducted. In terms of prevalence in official record crime statistics, the results show that a large majority of the organized crime offenders' sons seem to follow in their fathers' footsteps. This is not the case for daughters, as half of them have a criminal record, but primarily for only one minor crime. Intergenerational transmission seems to be facilitated by mediating risk factors, inadequate parenting skills of the mother, the "famous" or violent reputation of the father, and deviant social learning. If we want to break the intergenerational chain of crime and violence, the results seem to suggest that an accumulation of protective factors seem to be effective, particularly for girls. For girls, supervision from a child protection service also seems to work quite well. For boys, we might need a different approach to prevent them from offending.